Nigeria - An Economic Analysis of Natural Resources Sustainability for the Mining Sector Component - Eyre, J. M. (World Bank, Washington, DC, 2012)
This report firstly presents an analysis of the Nigerian economy as the environment within which the solid minerals sector is situated. It discusses the economy in terms of its distinguishing characteristics, structure and related issues, such that the place of the sold minerals sector can be appreciated. An examination of policy issues and economic reforms to aid the development process is also presented. This study, carried out between February and April 2007, specifically addresses the prospects of developing an industrial mining sector in Nigeria. The current mining sector is dominated by small-scale operations, working below their full potential and literally scratching the surface. Preliminary investigations indicated a lack of up to date information on deposits and lack of microeconomic information on the feasibility of extraction. The study is considered to be important from two different perspectives. First, solid mineral resources are economically, socially and environmentally crucial for Nigeria. There are key knowledge gaps in the sector. In addition the utilization of solid mineral resources is well aligned with the Bank's country partnership strategy, which is placing a strong focus on nonoil growth sectors of the economy. The other perspective comes from the environmental sector; the Bank has just completed the CEA (Country Environmental Analysis) and the idea is to continue the policy dialogue with the mining sector, and to help strengthen its links to the economic sectors where the environment is important. This study provides a major opportunity to carry this out. The primary objective of the study is to assess the prospects of an industrial mining sector emerging in Nigeria given what is known about the country's geology and mineral endowment as well as economic, institutional and other factors.